2016
DOI: 10.18178/ijfe.2.1.31-35
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Safety Evaluation of Exopolysaccharide Produced by Rhodotorula minuta BIOTECH 2178

Abstract: Yeast exopolysaccharide (EPS) are composed of unique sugar units, which offers an interesting perspective with respect to various food applications. This study aimed to characterize the EPS from Rhodotorula minuta BIOTECH 2178. Toxicological assessment of the EPS was investigated to ensure that it is safe for human consumption. The yeast EPS revealed high total sugar composition (59.21-62-47%) and low protein content (17.19%). FTIR spectrum showed prominent functional group such as hydroxyl, carboxyl, beta-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
3
11
0
2
Order By: Relevance
“…[32][33][34] Ramirez suggested that EPS of porous nature can be used as a thickener, texturizer, viscosifier and stabilizing agent in food industry. 4 The water holding capacity of the EPSs was 519 ± 18.5%. This was greater than that of EPS produced by Leuconostoc lactis KC117496 and Lactobacillus kefiranofaciens ZW3 (117% and 496%, respectively).…”
Section: Morphology and Water Holding Capacity Of Epssmentioning
confidence: 97%
See 1 more Smart Citation
“…[32][33][34] Ramirez suggested that EPS of porous nature can be used as a thickener, texturizer, viscosifier and stabilizing agent in food industry. 4 The water holding capacity of the EPSs was 519 ± 18.5%. This was greater than that of EPS produced by Leuconostoc lactis KC117496 and Lactobacillus kefiranofaciens ZW3 (117% and 496%, respectively).…”
Section: Morphology and Water Holding Capacity Of Epssmentioning
confidence: 97%
“…25 The absorption bands at 1093.86 cm -1 , 1129.2 cm -1 and 1140.7 cm -1 were corresponded to the C-O stretching vibrations and might be attributed to the ether group of polysaccharides or could be assigned to beta-glycosidic linkages. 4 The absence of peak at 1726 cm -1 demonstrated that the EPSs had no uronic acid. 25…”
Section: Ft-irmentioning
confidence: 98%
“…Samples were observed every 24 h interval for the biomass and the yield of EPS. Biomass was removed by centrifugation, and the EPS in the supernatant was precipitated using ethanol (96%) and then centrifuged at 5000 rpm for 5 minutes (Ramirez 2016). The EPS was then dialyzed for 24 hours against water to remove any remaining low molecular weight compounds, and freezedried using a Virtis Advantage Plus freeze-dryer (SP scientific, Warminster, USA).…”
Section: Production Of Exopolysaccharidementioning
confidence: 99%
“…Üretilen EPS'lerin gıda sektöründe ilave edildiği gıdanın yapısını düzenleyen, kalite özelliklerine olumlu etki gösteren bir katkı maddesi olmasının yanı sıra; insan sağlığı üzerine de pek çok faydası bildirilmiştir. Bu etkiler arasında özellikle mayalardan gelen mannanların, antioksidatif, antiviral, antimutajenik, prebiyotik, kolestrol düşürücü ve ağır metal tutucu özellik bulunmaktadır (Ksonzeková ve ark., 2016;Ramirez, 2016).…”
Section: Probiyotik öZellik Gösteren Diğer Maya Türleriunclassified
“…Ayrıca EPS'lerin probiyotik mikroorganizmalar tarafından üretilen kısa zincirli yağ asitleri ile birlikte sindirim sisteminde iyi bir prebiyotik etki gösterdiği de bildirilmiştir (Badel ve ark., 2011). Probiyotik özellikler açısından bakıldığında EPS üretiminin, sindirim sistemi boyunca karşılaşılan asit ve safra gibi etkenlere dayanım, uzun süre canlı kalabilme ve bulunduğu ortamda çoğalarak kolonize olma açısından son derece etkili olduğu bildirilmiştir (Ramirez, 2016). Ayrıca EPS'lerin prebiyotik potansiyeli ve bağırsak epiteline tutunmayı kolaylaştırma özellikleri de Sarıkaya ve ark.…”
Section: Probiyotik öZellik Gösteren Diğer Maya Türleriunclassified